Reverse switching from the biosimilar SB2 to the originator infliximab in previously switched patients with inflammatory bowel diseases: results of a prospective long-term cohort study - Sarah Fischer; Moritz Donhauser; Sarah Cohnen; Konstantin Fietkau; Marcel Vetter; Maria Grübel-Liehr; Peter Dietrich; Timo Rath; Angelika Wilfer; Ludmilla Sologub; Sabine Krebs; Frank Dörje; et al. (Therapeutic Advances in Gastroenterology)
Background: Data regarding multiple switches including reverse switching between infliximab and its biosimilars are scarce in the field of inflammatory bowel diseases (IBD). Objectives: We investigated the clinical effectiveness as primary outcome measure after repeated switches. Secondary endpoints included C-reactive protein (CRP) levels, immunogenicity (trough levels (TL); anti-drug antibodies (ADA), safety and drug persistence. Design: This study is a prospective, single-centre, observational cohort study. IBD patients receiving originator infliximab were switched to biosimilar SB2 and then reverse switched after 96 weeks and followed up for another 48 weeks. Methods: Clinical disease activity (Harvey–Bradshaw-index (HBI) in Crohn’s disease (CD), partial Mayo score (pMS) in ulcerative colitis (UC)), CRP, TL, ADA, therapy-discontinuations and (serious) adverse events ((S)AE)) were monitored throughout the study. Results: Ninety-five patients (60 CD, 38 female) were enrolled. The median HBI was 2 (interquartile range (IQR) 1–4) at baseline and 2 (1–4) at week 48, resulting in a mean intra-individual change of 0.0 (standard deviation (SD) 1.5). The median pMS was 1 (IQR 0–1) at baseline and 0.5 (0–1) at week 48 resulting in a mean intra-individual change of 0.0 (SD 0.8). Clinical remission was achieved in 80% at baseline and 82% at week 48. Median CRP 2.0 mg/l (IQR 1.0–4.1) at baseline and 2.4 mg/l (1.1–5.2) at week 48 resulted in a mean change of 1.7 (SD 5.8) and no significant differences in CD ( p  = 0.3) and UC ( p  = 0.9). Median TL were 7.2 µg/ml (IQR 3.8–19.3) at baseline and 5.5 µg/ml (3.5–13.1) at week 48, resulting in a mean change of −1.0 (SD 7.4) with no statistical significance (CD p  = 0.26, UC p  = 0.41). De-novo-ADA were developed by 3.4%. The discontinuation rate was 14.7%. Safety signals were consistent with previous studies. Conclusion: Reverse switching had no impact on efficacy of infliximab therapy in our cohort of IBD patients. The switch didn’t influence immunogenicity or safety of therapy.